PENGARUH PERINGKAT OBLIGASI, DEBT TO EQUITY RATIO DAN UKURAN PERUSAHAAN TERHADAP YIELD TO MATURITY OBLIGASI KORPORASI DENGAN TINGKAT SUKU BUNGA SBI SEBAGAI VARIABEL MODERATING - Situmorang, Bornok (Jurnal Terapan Manajemen dan Bisnis, 2017)
Result of this research are: Bond Rating have no negative and significant influence to Yield to Maturity becouse sigficant value more than 0,05 and similarly t count is less than t table.  Debt to Equity Ratio have no positive and significant influence to Yield to Maturity becouse sigficant value more than 0,05 and similarly t count is less than t table.  Firm Size have no negative and significant influence to Yield to Maturity becouse sigficant value more than 0,05 and similarly t count is less than t table.  SBI Rate have positive and significant influence to Yield to Maturity becouse sigficant value less than 0,05 and similarly t count is more than t table with positive coeffisien direction .  Result of moderating test show that SBI Rate constitutes moderator variable for the relationship of Bond Rating with Yield to Maturity and the relationship of Debt to Equity Ratio with Yield to Maturity but its not moderator variable for the relationship of Firm Size with Yield to Maturity.